Effectiveness of the Implementation of the Program Keluarga Harapan (PKH) in Poverty Alleviation Efforts (Case Study in Krangkeng Sub-district, Indramayu Regency) : Efektivitas Pelaksanaan Program Keluarga Harapan (PKH) dalam Upaya Pengentasan Kemiskinan (Studi Kasus di Kecamatan Krangkeng, Kabupaten Indramayu) - udinsyarifudin syarifudin (Metafora: Education, Social Sciences and Humanities Journal, 2026)
Poverty remains a multidimensional challenge in Indonesia, particularly in rural areas characterized by limited access to education, health services, and economic opportunities. The Program Keluarga Harapan (PKH), a conditional cash transfer program introduced by the Indonesian government, aims to alleviate poverty and improve human capital among low-income households. However, studies on PKH have largely focused on general outcomes, while limited attention has been given to how local implementation dynamics shape program effectiveness in specific rural contexts. This study examines the effectiveness of PKH implementation in poverty alleviation in Krangkeng Indramayu. This research employed a qualitative case study approach using in-depth interviews, observation, and documentation. Informants included beneficiary households, program coordinators, and PKH facilitators. The findings indicate that PKH implementation has been effective in reducing household expenditure burdens, improving access to education and health services, and encouraging behavioral changes among beneficiaries. Program effectiveness is supported by facilitator competence, local government support, and beneficiary participation. This study highlights the importance of local governance and community-based implementation in shaping PKH effectiveness and proposes strengthening facilitator capacity, improving data accuracy, and enhancing economic empowerment initiatives to improve long-term poverty alleviation outcomes.